LACK OF CYTOTOXICITY BY TRUSTWATER ECASOL? USED TO MAINTAIN GOOD QUALITY DENTAL UNIT WATERLINE OUTPUT WATER IN KERATINOCYTE MONOLAYER AND RECONSTITUTED HUMAN ORAL EPITHELIAL TISSUE MODELS - COLEMAN, DAVID; RUSSELL, RONALD; BOYLE, MARIA; O'DONNELL, MARY (My University, 2010)
Summary: We previously showed that residual treatment of dental chair unit (DCU) supply water using the electrochemically-activated solution Trustwater Ecasol? (2.5 ppm) provided an effective long-term solution to the problem of dental unit waterline (DUWL) biofilm resulting in DUWL output water quality consistently superior to potable water. Objectives: To investigate the cytoxicity of Ecasol using cultured keratinocyte monolayers and reconstituted human oral epithelial (RHE) tissue and to extend the study of Ecasol's effectiveness in maintaining the microbiological quality of DUWL output water. Methods: TR146 human keratinocyte monolayers and RHE tissues were exposed to Ecasol (2.5-100 ppm) for 1 h periods after removal of growth medium and washing with phosphate buffered saline (PBS). Experiments were repeated using Ecasol that had been exposed for 30 min to 1-2 ?g/mL bovine serum albumin (BSA), equivalent to protein concentrations in saliva. To quantitatively determine cytotoxic effects on monolayers following Ecasol exposure, the Alamar Blue proliferation assay (assesses cell viability) and the Trypan Blue exclusion assay (assesses plasma membrane integrity), were used. Cytotoxicity effects on RHE tissues were assessed by the Alamar Blue assay and by histopathology. Results: Ecasol at >5.0 ppm resulted in significant (P < 0.001) cytotoxicity to keratinocyte monolayers following a 1 h exposure. These effects, however, were completely negated by BSA pretreatment of Ecasol. No cytotoxicity was observed in the more complex RHE tissue at any of the Ecasol concentrations tested. In a 60-week study of 10 DCUs, tested weekly, the average density of aerobic heterotrophic bacteria in Ecasol-treated (2.5 ppm) DCU supply water was < 1 cfu/mL and in DUWL output water was 6.5 cfu/mL. Conclusions: Ecasol present as a residual disinfectant in DUWL output water is very unlikely to have adverse effects on human oral tissues at levels effective in maintaining DUWL output water quality at better than potable standard water quality.
PUBLISHED
Keywords: Dentistry; dental chair unit (DCU) supply water; Immunology, Inflammation & Infection